Transport current density performance of doped TL1212 superconductor tapes in magnetic field / Mohd Isa Mohd Yusof, Ahmad Kamal Hayati Yahya and Syed Yusainee Syed Yahya - Mohd Yusof, Mohd Isa; Yahya, Ahmad Kamal Hayati; Syed Yahya, Syed Yusainee (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
Superconducting powder from high purity chemicals with nominal composition of Tlo.gBio.iSri.glno.iCaosiYo.iQ^Oy were used to fabricate Tl-1212/Ag superconducting tapes using the dip-coating (DC) method. The tapes were subjected to reannealing under different heating conditions where some of the tapes were subjected to intermediate mechanical rolling. Results showed that annealing temperature together with intermediate mechanical rolling (IR) could be optimized to increase Tc and 1212 phase formation and Jc of In-substituted Tl-1212/Ag tapes. The highest Jc was observed for the tape, which was reannealed at 910 °C for a total duration of 60 minutes and subjected to IR. The increased Jc could be due to the densification of superconducting core and the increase in 1212 phase after thermomechanical treatment. The performance of Jc of the tapes in external magnetic fields showed existence of weak links at low fields (< 0.2 T) followed by strong links which are dominant at higher fields.